(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This research aims to analyze and describe: (1) the awareness of the support teachers on the sensory circuit program, and (2) the adaptability of support teachers in using the sensory circuit program as a model of classroom management to cope with behavioral problems of special needs students at XYZ School South Kembangan. The research used ten indicators, fourteen questions, and five informants with an evaluation study approach. The data validity is obtained using triangulation techniques, informants’ analysis, and comparing relevant theories related and previous research. Analysis of the interview result consists of nine related quotations of awareness and twenty related quotations of adaptability showed that four out of five support teachers’ levels of awareness and adaptability are increasing. The result also found the influenced factors of the teachers’ awareness and adaptability level which included (1) consistency of hands-on practice, (2) students’ background needs, and (3) good teamwork.